2016
DOI: 10.1007/s00484-016-1133-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of atmospheric warming on grapevine phenology and post-harvest heat accumulation across a range of climates

Abstract: Carbohydrates are accumulated within the perennial structure of grapevines when their production exceeds the requirements of reproduction and growth. The period between harvest and leaf-fall (the post-harvest period) is a key period for carbohydrate accumulation in relatively warmer grape-growing regions. The level of carbohydrate reserves available for utilisation in the following season has an important effect on canopy growth and yield potential and is therefore an important consideration in vineyard manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…They may also modify the limits of winegrowing regions, such as those of Denomination of Origin (MORIONDO et al, 2013). With regard to grapevine phenology, they may change the dates of budbreak, flowering, veraison, maturity and leaf fall (VINK et al, 2012;CABRÉ et al, 2016;HALL et al, 2016;RUML et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also modify the limits of winegrowing regions, such as those of Denomination of Origin (MORIONDO et al, 2013). With regard to grapevine phenology, they may change the dates of budbreak, flowering, veraison, maturity and leaf fall (VINK et al, 2012;CABRÉ et al, 2016;HALL et al, 2016;RUML et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The growing degree day (GDD) is used in this case (WINKLER et al, 1974) to determine the thermal needs of a plant to ripen grapes from vine budbreak. Indeed, there is a positive correlation between the increase of air temperature and vine phenology (HALL et al, 2016). The accumulated GDD may vary in response to the cultivar, region, climatic conditions and cultural practices performed in the vineyard.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect of crop development was not investigated here and needs more research. Mounzer et al () confirmed that use of growing degree days, which express phenological stages on a standardised scale, rather than the number of days or a calendar, permits comparisons to be made between different years and geographical areas (Hall et al, ). Therefore, further research is required to understand the impact of temperature in conjunction with other environmental factors on phenology of Indian jujube.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study of crop phenology has become more important because of climate change. Climate change can alter the duration of a crop cycle such that adjustments in timing of various crop management practices are required (Hall, Mathews, & Holzapfel, ; Olesen et al, ; Ramírez & Kallarackal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change can change the length of the crop cycle, and knowledge of the sum of degree days combined with the phenological phases becomes an important tool to determine the necessary adjustments for crop management (Hall et al, ; Ramírez & Kallarackal, ). Air temperature is the main meteorological factor affecting the development of agricultural crops (Gramig & Stoltenberg, ; Mendes et al, ; Streck, ).…”
Section: Discussionmentioning
confidence: 99%